Telecommuting as a Sustainable Transportation Measure in Ecuador - Corral Naveda, Alvaro Nicolás (Enfoque UTE, 2022)
The purpose of this article is to provide information to determine that telecommuting in Ecuador can be used as a measure of sustainable transport. Briefly, sustainable development is described, and certain definitions and approaches related to sustainable transport are covered, for instance, the Avoid-Shift-Improve (ASI) approach, as well as the Transport Demand Management (TDM), which serve to validate from a conceptual point of view the application and usefulness of telecommuting. An overview of the current situation in the transport sector in Ecuador is analyzed; the final energy demand; the environmental aspects related to transport, and the amount of public and private employees that are telecommuting. Taking into consideration some hypothesis, such as car ownership rate, the total amount of kilometers driven per year, the assumption of the distance travelled by employees who take public transportation; the assumptions helped to determine the savings that can be obtained through telecommuting in the present time. Therefore, these results would provide adequate information for decision makers to establish a conclusive pronouncement on whether or not support telecommuting as a valid working approach, and to develop the necessary policies to maintain it over time.